If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + 8 = -3(5x + -7) Combine like terms: 13 + 8 = 21 21 = -3(5x + -7) Reorder the terms: 21 = -3(-7 + 5x) 21 = (-7 * -3 + 5x * -3) 21 = (21 + -15x) Add '-21' to each side of the equation. 21 + -21 = 21 + -21 + -15x Combine like terms: 21 + -21 = 0 0 = 21 + -21 + -15x Combine like terms: 21 + -21 = 0 0 = 0 + -15x 0 = -15x Solving 0 = -15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15x' to each side of the equation. 0 + 15x = -15x + 15x Remove the zero: 15x = -15x + 15x Combine like terms: -15x + 15x = 0 15x = 0 Divide each side by '15'. x = 0 Simplifying x = 0
| 15-5/2=9+1/2x | | -0.9x+1.93=-0.7x+6.73 | | x+2=2.3 | | (x+y)+(4y+x)=180 | | 3x^2=-42x | | 3x^2+7x=5x-7 | | 3x+y=.9 | | 2x+47=14 | | -7(y^2+18y+81)=-1372 | | 6f=-2f-8 | | 5x-2(x-5)=7 | | x+y=2.3 | | 2/5x^2-6=-4/5x | | 6x-12=4x-6 | | 4(8w+2)-5(4w+2)= | | 1/2x-12=4/3x+6 | | 7x+4=5x+3x-3 | | 4y-12+7y+16=180 | | x+3=5y+4 | | 900=-4x+967 | | 5x-10=5y | | 5/6=(y-6)/(y+1) | | x/3+10=24 | | 3f=-f-6 | | 3m+9m=10(11+3m)-9(6+2m) | | 5x-32=15x-88 | | 7(y-3)=4y-39 | | 2c+6/-2=18 | | 3x+5+4x-35=180 | | 2x-5=4x-11 | | (n+4)*7=66 | | 7x^2+46x=21 |